2014
DOI: 10.3233/bme-141032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrofluoric acid (HF) concentration to pores size diameter of silicon membrane

Abstract: This paper studies parameters which affect the pore size diameter of a silicon membrane. Electrochemical etching is performed in characterise the parameter involved in this process. The parameter has been studied is volume ratio of hydrofluoric acid (HF) and ethanol as an electrolyte aqueous for electrochemical etch. This electrolyte aqueous solution has been mixed between HF and ethanol with volume ratio 3:7, 5:5, 7:3 and 9:1. As a result, the higher volume of HF in this electrolyte gives the smallest pore si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The facial area of silicon membrane exposed to the electrolyte solution was 1 cm × 1 cm. High current density contributed to columnar structure formation, while HF concentration contributed to pore size [41]. Alternately, mixture between HF and DMF can also produce columnar structure on silicon [42].…”
Section: Pore Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…The facial area of silicon membrane exposed to the electrolyte solution was 1 cm × 1 cm. High current density contributed to columnar structure formation, while HF concentration contributed to pore size [41]. Alternately, mixture between HF and DMF can also produce columnar structure on silicon [42].…”
Section: Pore Characterizationmentioning
confidence: 97%
“…For our application, the pore holes has to be columnar, with pore sizes of less than 50 nm. Our previous work has shown that pore sizes and uniformity are reproducible given the specific set of parameters [33,40,41].…”
Section: Ece Processmentioning
confidence: 99%
“…The aim of this research was to separate biological particles from the membranes for use as an artificial kidney. It has been noted in a previous research work by (Burham et al 2014a(Burham et al , 2014b) that the silicon membranes had some flaws as the biological particles tend to clog. Therefore, application of dielectrophoresis will be used to improve and separate the biological particles.…”
Section: Introductionmentioning
confidence: 95%
“…Various methods to realize a nano size filtration trench have been reported before. As an example, Burham et al (2014) uses electrochemical etching to form nano scale trenches but then the produced trenches are not uniform in size plus challenging to reproduce precise same trench size and trench-to-trench gap which is not favorable for mass production. In the other hand, for the fabrication of uniform trenches; electron beam lithography, focused ion beam etching, and nanoimprint lithography might be used (Nabar et al 2012;Tong et al 2004).…”
Section: Introductionmentioning
confidence: 99%